Influence of Fiber Stiffness on Meniscal Cell Migration into Dense Fibrous Networks. Issue 8 (23rd December 2019) - Song, Kwang Hoon; Heo, Su‐Jin; Peredo, Ana P.; Davidson, Matthew D.; Mauck, Robert L.; Burdick, Jason A.
Abstract: Fibrous scaffolds fabricated via electrospinning are being explored to repair injuries within dense connective tissues. However, there is still much to be understood regarding the appropriate scaffold properties that best support tissue repair. In this study, the influence of the stiffness of electrospun fibers on cell invasion into fibrous scaffolds is investigated. Specifically, soft and stiff electrospun fibrous networks are fabricated from crosslinked methacrylated hyaluronic acid (MeHA), where the stiffness is altered via the extent of MeHA crosslinking. Meniscal fibrochondrocyte (MFC) adhesion and migration into fibrous networks are investigated, where the softer MeHA fibrous networks are easily deformed and densified through cellular tractions and the stiffer MeHA fibrous networks support ≈50% greater MFC invasion over weeks when placed adjacent to meniscal tissue. When the scaffolds are sandwiched between meniscal tissues and implanted subcutaneously, the stiffer MeHA fibrous networks again support enhanced cellular invasion and greater collagen deposition after 4 weeks when compared to the softer MeHA fibrous networks. These results indicate that the mechanics and deformability of fibrous networks likely alter cellular interactions and invasion, providing an important design parameter toward the engineering of scaffolds for tissue repair. Abstract : Electrospun fibrous hydrogels are being developed for meniscal tissue repair. To better understand the influence of scaffold biophysical properties on cellular invasion, fiber stiffness is varied. Softer networks are easily deformed by cells to densify fibers, whereas stiffer networks support increased cell invasion both by seeded cells and when placed adjacent to meniscus tissue.